Pengaruh Carbon Emission Disclosure terhadap Nilai Perusahaan dengan Kinerja Lingkungan sebagai Variabel Moderasi (Studi pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022) - Shafira, Tastafti Mauliana (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Carbon Emission raises public awareness about the negative impacts resulting from corporate activities. Pressure and demands from various parties are expected to influence the company's image and performance in the future. Information regarding the company's environmental performance will be an important consideration for investors in making investment decisions. This study aims to examine the impact of Carbon Emission Disclosure and environmental performance on the value of energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022. The data analysis method uses panel data regression analysis and moderation regression analysis with Eviews software, involving several stages of testing. Based on the analysis results, a significant negative impact was found between the level of carbon emission disclosure and the company’s value. Although the current environmental performance does not show a significant effect on the company’s value, companies still need to optimize their environmental performance. Improving environmental performance can contribute to a better company image and potential long-term benefits that may not yet be directly reflected in the current company value.